2011
DOI: 10.1002/ana.22414
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of intraocular and intracranial pressure: Is there a relationship?

Abstract: No significant relationship between ICP and IOP was observed. Noninvasive IOP measurements do not predict ICP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 16 publications
1
31
2
2
Order By: Relevance
“…The remaining 12 studies enrolling 546 participants identified in our literature search were included in our meta-analysis (Table 1). 2,4,5,11,15,16,19,24,25,31,32,35,36 Although all of these 12 studies contributed to the calculation of a pooled estimated correlation coefficient, only 4 presented outcomes required for the calculation of summary diagnostic accuracy estimates (Table 2). 16,19,25,36 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 12 studies enrolling 546 participants identified in our literature search were included in our meta-analysis (Table 1). 2,4,5,11,15,16,19,24,25,31,32,35,36 Although all of these 12 studies contributed to the calculation of a pooled estimated correlation coefficient, only 4 presented outcomes required for the calculation of summary diagnostic accuracy estimates (Table 2). 16,19,25,36 …”
Section: Resultsmentioning
confidence: 99%
“…Patients were recruited from outpatient neurology clinics, 11,15,19,31,32 the emergency department (ED), 25 and intensive care units (ICUs). Participants were adult patients with the exception of 1 study performed in a pediatric ICU setting.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some investigators have argued that IOP is correlated with ICP (Lashutka et al, 2004;Li et al, 2012), but others argue that they are unrelated (Czarnik et al, 2009;Kirk et al, 2011). Still others have concluded that, although there is a correlation between ICP and IOP, IOP is a "poor predictor" of ICP (Golan et al, 2013;Spentzas et al, 2010;Yavin et al, 2014).…”
Section: Figure 4 Pressures Around the Optic Nerve (On)mentioning
confidence: 99%